Endophthalmitis after cataract surgery: results from seven years of epidemiological surveillance - Reginaldo Adalberto Luz; Lincoln Pereira S. Dall'Oglio; Flávia Sotolani Silva; Wagner Ghirelli; Maria Clara Padoveze (Revista Brasileira de Oftalmologia, 2019)
Abstract Purpose: This study aims to describe the incidence, clinical presentation, and evolution of endophthalmitis cases occurred at an ophthalmologic center in Brazil. Methods: This is a review of medical records of patients undergoing cataract surgery from 2008 to 2014. Clinical variables associated with the outcome of postoperative endophthalmitis were evaluated. Results: during the study period, 27,609 cataract surgeries were performed. It was identified 35 cases of endophthalmitis. The overall incidence of endophthalmitis was 0.13%, with an annual variation from 0.04% to 0.27%. The main signs and symptoms in patients with endophthalmitis were ocular pain and low visual acuity associated with conjunctival hyperemia and hypopyon. Gram-positive microorganisms were the most frequent etiological agents. All patients received an intra-vitreous injection of antibiotics as immediate treatment. The final visual acuity was equal to or worse than the ability to count the examiner's fingers in 57.1% of the patients. Evisceration or enucleation was required in 3 patients. Conclusion: The incidence of endophthalmitis and the majority of signs and symptoms found in this study were in agreement with literature in the field. Although the incidence rate is low, the loss of vision experienced by most patients with endophthalmitis after cataract surgery highlights the need for efforts to prevent infection and early diagnosis to avoid such complications.